Factors influencing patients' satisfaction at different levels of health facilities in Bangladesh: Results from patient exit interviews - Adhikary, G; Shawon, MSR; Ali, MW; Shamsuzzaman, M; Ahmed, S; Shackelford, KA; Woldeab, A; Alam, N; Lim, SS; Levine, A; Gakidou, E; Uddin, MJ (Public Library of Science, 2018)
There is a paucity in current literature about the level of patients' satisfaction and factors influencing it in Bangladesh health system. We aimed to measure the level of patients' satisfaction across different types and levels of healthcare facilities and to determine which factors influence this satisfaction level. A patient exit interview was carried out among 2207 patients attending selected health facilities in two administrative divisions of Bangladesh, namely Rajshahi and Sylhet. Information on healthcare experience and satisfaction with received care was collected through an electronic structured questionnaire. Information about 'overall satisfaction with healthcare' was collected on a 10-point scale and then dichotomized based on the median-split. Binomial logistic regressions, both simple and multivariable, were conducted to identify which factors contribute significantly to patients' satisfaction. We found that 63.2% of the participants were satisfied with the healthcare service they received. Patients attending the private facilities had the highest level of satisfaction (i.e. 73%) and patients attending the primary care facilities had the lowest level of satisfaction (i.e. 52%). Factors like convenient opening hours, asking related questions to the providers, facility cleanliness and privacy settings were significantly associated with patients' satisfaction. Being satisfied with facility cleanliness (multivariable OR 4.30; 95% CI: 3.29-5.62) and privacy settings (multivariable OR 1.68; 95% CI: 1.28-2.21) were the strongest predictors of patients' satisfaction. In conclusion, a significant portion of the patients in Bangladesh are not satisfied with their received care. Patients' satisfaction can be increased by focusing on improving facility cleanliness, privacy settings and providers' interpersonal skills.